1989
DOI: 10.1152/jappl.1989.66.4.1800
|View full text |Cite
|
Sign up to set email alerts
|

Collapsibility of the human upper airway during normal sleep

Abstract: Upper airway resistance (UAR) increases in normal subjects during the transition from wakefulness to sleep. To examine the influence of sleep on upper airway collapsibility, inspiratory UAR (epiglottis to nares) and genioglossus electromyogram (EMG) were measured in six healthy men before and during inspiratory resistive loading. UAR increased significantly (P less than 0.05) from wakefulness to non-rapid-eye-movement (NREM) sleep [3.1 +/- 0.4 to 11.7 +/- 3.5 (SE) cmH2O.1-1.s]. Resistive load application durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
4

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 0 publications
6
72
1
4
Order By: Relevance
“…Thus, there was no additional effect of REM sleep on baseline retropalatal dimensions. This finding is corroborated by previous studies which have found that upper airway resistance during REM sleep was the same (Hudgel et al 1984;Wiegand et al 1989) or less than (Wiegand et al 1990a) that seen during NREM sleep. Our study also showed a similar finding, with a trend for the RUA at a fixed flow of 0·1 l s¢ to be less during REM sleep than during NREM sleep.…”
Section: The Effect Of Rem Sleep On the Upper Airwaysupporting
confidence: 89%
“…Thus, there was no additional effect of REM sleep on baseline retropalatal dimensions. This finding is corroborated by previous studies which have found that upper airway resistance during REM sleep was the same (Hudgel et al 1984;Wiegand et al 1989) or less than (Wiegand et al 1990a) that seen during NREM sleep. Our study also showed a similar finding, with a trend for the RUA at a fixed flow of 0·1 l s¢ to be less during REM sleep than during NREM sleep.…”
Section: The Effect Of Rem Sleep On the Upper Airwaysupporting
confidence: 89%
“…A sleepinduced increase in upper airway resistance, in the absence of immediate load compensation, seems to be an important determinant of CO 2 retention [44]. The changes in upper airway resistance, observed in normal subjects, may be quite variable [45]. The higher the CO 2 apnoeic threshold, the more central apnoeas will occur during sleep.…”
Section: Co 2 Thresholdmentioning
confidence: 99%
“…[17][18][19] Ethanol has been shown to increase both waking and sleeping upper airway resistance. Robinson and associates 20 showed that the same dose of ethanol used in our study increased the upper airway resistance of healthy waking subjects by about 75% at 45 min after the drink and that the resistance was back to near the baseline level at 90 min.…”
Section: Effects On Airway Resistancementioning
confidence: 99%